Health Education and Its Influence on Pregnant Women’s Knowledge of Danger Signs in Pregnancy - Atalia Pili Mangngi; Ni Putu Indu Dewi Pradnyani Murti; Ermi Lilianda Alang; Ninick Corea Fernandez (International Journal of Health and Social Behavior, 2026)
Maternal Mortality Rate (MMR) is a critical indicator for evaluating maternal health programs, and insufficient knowledge of pregnancy danger signs remains a significant factor in preventable maternal complications and mortality. This issue is particularly prevalent among third-trimester pregnant women. Health education has proven to be an effective strategy for enhancing maternal knowledge, promoting early detection of obstetric emergencies, and supporting timely decision-making. This study aimed to evaluate the impact of health education on improving knowledge of pregnancy danger signs among third-trimester pregnant women in Nunkurus Village. A pre-experimental study with a one-group pre-test–post-test design was conducted, involving 42 third-trimester pregnant women, with 40 selected through purposive sampling. Structured questionnaires were used to collect primary data, and the Wilcoxon signed-rank test was employed to analyze the knowledge differences before and after the intervention. Results showed a statistically significant increase in knowledge after the health education intervention (p-value = 0.000; p < 0.05). In conclusion, health education significantly enhances knowledge of pregnancy danger signs among third-trimester pregnant women. Strengthening community-level educational interventions can help in early detection of pregnancy complications and contribute to reducing maternal morbidity and mortality.